GAYA BAHASA PERSONIFIKASI DALAM LIRIK LAGU ONE DAY - Wini Widianti; Fenny Febrianty (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2021)
This research aims to analyze the personification style and describe the function of the personification style in the lyrics of the song entitled One Day. This research uses a literary stylistic approach. The type of research used in this research is library research. This research uses a descriptive analysis method, which is performed by explaining the data and then proceeded with the analysis of language style using rhetorical theory by Seto (2015) and language style function using Keraf theory (2010). Data sources in this research are divided into two, primary data and secondary data. Primary data are also divided into two, material objects in the form of lyrics of the song One Day by 3RACHA and Lee Jun Seok, and formal objects in the form of rhetoric. While secondary data is formed from books reference and obtained data from the Internet. The results of this research indicate that there are six forms of the style of personification in the lyrics of the song One Day, there are on the 2nd stanza of the 1st line, the 3rd stanza of the 5th line, the 4th stanza of the first line, the 2nd line, the 8th stanza of the 1st line and the 8th stanza of the 2nd line. The function of personification in the lyrics of this song is to liven up lifeless objects.